High hydrostatic pressure induces atrial electrical remodeling through angiotensin upregulation mediating FAK/Src pathway activation. (March 2020) - Li, Xin; Deng, Chun-Yu; Xue, Yu-Mei; Yang, Hui; Wei, Wei; Liu, Fang-Zhou; Guo, Hui-Ming; Liu, Yang; Wang, Zhao-Yu; Zhang, Meng-Zhen; Wu, Shu-Lin; Rao, Fang
Abstract: Hypertension is an independent risk factor for atrial fibrillation (AF), although its specific mechanisms remain unclear. Previous research has been focused on cyclic stretch, ignoring the role of high hydrostatic pressure. The present study aimed to explore the effect of high hydrostatic pressure stimulation on electrical remodeling in atrial myocytes and its potential signaling pathways. Experiments were performed on left atrial appendages from patients with chronic AF or sinus rhythm, spontaneously hypertensive rats (SHRs) treated with or without valsartan (10 mg/kg/day) and HL-1 cells were exposed to high hydrostatic pressure using a self-developed device. Whole-cell patch-clamp recordings and western blots demonstrated that the amplitudes of ICa, L, Ito, and IKur were reduced in AF patients with corresponding changes in protein expression. Angiotensin protein levels increased and Ang1–7 decreased, while focal adhesion kinase (FAK) and Src kinase were enhanced in atrial tissue from AF patients and SHRs. After rapid atrial pacing, AF inducibility in SHR was significantly higher, accompanied by a decrease in ICa, L, upregulation of Ito and IKur, and a shortened action potential duration. Angiotensin upregulation and FAK/Src activation in SHR were inhibited by angiotensin type 1 receptor inhibitor valsartan, thus, preventing electrical remodeling and reducing AF susceptibility. These results were verified in HL-1 cells treated with high hydrostatic pressure, and demonstrated that electrical remodeling regulated by the FAK-Src pathway could be modulated by valsartan. The present study indicated that high hydrostatic pressure stimulation increases AF susceptibility by activating the renin-angiotensin system and FAK-Src pathway in atrial myocytes. Graphical abstract: Unlabelled Image Highlights: To explore the direct effects of hydrostatic pressure on the pathogenesis of AF. High-pressure increased AF susceptibility by altering ICa, L, Ito, IKur and APD. Ang II-AT1R was involved in high-pressure induced atrial electrical remodeling. FAK-Src was the potential signaling pathway and regulated by Ang II-AT1R.